Perilaku belanja online dan niat beli pada generasi “Z” di Indonesia - Soni Harsono; Nathan Tidiend Haripraditya; Much Aji Rochman Soleh (Journal of Business & Banking, 2022)
Generation Z that dominates the population and the development of e-commerce has changed their shopping patterns, especially in terms of purchase intention. For example they choose to shop online. This study has two objectives, frst: to examine the impact of attitudes, beliefs, value motives and social motives on online purchase intentions. Second, to examine the effect of attitudes, beliefs, value motives and social motives on purchase intentions moderated by subjective norms. Data were collected from 360 respondents and analyzed using the partial least squares structural equation model (PLS-SEM) method. It was found that online purchase intentions are inﬂuenced by attitudes, beliefs, value motives, and social motives. The results further reveal that subjective norms have a moderating effect on trust with online purchase intentions. However, subjective norms have no moderating effect on attitudes, value motives and social motives with online purchase intentions. This research is benefcial for understanding the online purchase intention behavior of Generation Z. It provides knowledge about consumer behavior and contributes methodologically through the introduction of the PLS approach.